PEMAKAIAN LEKSEM MATA DALAM BAHASA INDONESIA - Darmini, Wiwik (STILISTIKA, 2012)
PEMAKAIAN LEKSEM MATA DALAM BAHASA INDONESIA Wiwik Darmini Abstract This study aims to: a. mendeskipsikan any unit that can join in Indonesian eyes leksem b. describe the meaning of the eyeleksem after joining the other units in Indonesian; c. describes the location of the hardness of the eye leksem after joining the otherunits in Bahasa Indonesian. The method used is descriptivemethod that seeks to examine kualitataif and provide a careful and thorough linguistic facts. Provision of data was done by usinglibraries, refer to the technique, reading techniques, and technicalnotes. This study used the method to analyze the distributionaldata. Results and discussion show that the units can be joinedwith the eyes can be broken down into leksem: First, the unit in the form of the word, can be specified: a) that form the compound36; b) a compound word formed instead of four; c) a unit thataffixes a morpheme there are 10; d) the other unit, which is not the type one and two of three; d) units that form the proverbsfound as many as 13. Second, the meaning leksem eye afterjoining the other units are given according to the meaning of meaning is in the Big Indonesian Dictionary. While that is aproverb meaning is taken from a book that discusses proverbs.Third, the location of the eye leksem after meeting with other unitstend to have a strong position that is likely to be reversed the order because it will lead to some other meaning or notacceptable in the Indonesian language. The location is not strongeye leksem usually joined with others to forma unit form over thewords in the syntactic level. Keywords: consumption, leksem eyes, the Indonesian language